2009
DOI: 10.1142/s1793830909000130
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the Joint Replenishment Problem With Deadlines

Abstract: The objective of the classical Joint Replenishment Problem (JRP) is to minimize ordering costs by combining orders in two stages, first at some retailers, and then at a warehouse. These orders are needed to satisfy demands that appear over time at the retailers. We investigate the natural special case that each demand has a deadline until when it needs to be satisfied. For this case, we present a randomized 5/3-approximation algorithm. We moreover prove that JRP with deadlines is APX-hard. Finally, we extend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…(They considered an equivalent problem of packet aggregation with deadlines on two-level trees.) Nonner and Souza [NS09] then showed that JRP-D is APX-hard, even if each retailer issues only three demands. Levi, Roundy and Shmoys [LRS06] gave a 2-approximation algorithm based on a primal-dual scheme.…”
Section: I} a Solution (Also Called A Schedule) Is A Set Of Ordementioning
confidence: 99%
See 3 more Smart Citations
“…(They considered an equivalent problem of packet aggregation with deadlines on two-level trees.) Nonner and Souza [NS09] then showed that JRP-D is APX-hard, even if each retailer issues only three demands. Levi, Roundy and Shmoys [LRS06] gave a 2-approximation algorithm based on a primal-dual scheme.…”
Section: I} a Solution (Also Called A Schedule) Is A Set Of Ordementioning
confidence: 99%
“…Levi, Roundy and Shmoys [LRS06] gave a 2-approximation algorithm based on a primal-dual scheme. Using randomized rounding, Levi et al [LRSS08,LS06] (building on [LRS05]) improved the approximation ratio to 1.8; Nonner and Souza [NS09] reduced it further to 5/3. These results use a natural linear-program (LP) relaxation, which we use too.…”
Section: I} a Solution (Also Called A Schedule) Is A Set Of Ordementioning
confidence: 99%
See 2 more Smart Citations
“…Constraints 13,14,16,17,19,7 are the same as in the LP for Uncapacitated SIRPFL. Constraint 15 requires that the number of trips to v on day s must be at least the total demand at v that were served from day s scaled by the capacity limit.…”
Section: B Capacitated Splittable Sirpflmentioning
confidence: 99%